2018
DOI: 10.1002/nag.2767
|View full text |Cite
|
Sign up to set email alerts
|

An approach for providing quasi‐convexity to yield functions and a generalized implicit integration scheme for isotropic constitutive models based on 2 unknowns

Abstract: Yield and plastic potential surfaces are often affected by problems related to convexity. One such problem is encountered when the yield surface that bounds the elastic domain is itself convex; however, convexity is lost when the surface expands to pass through stress points outside the current elastic domain. In this paper, a technique is proposed, which effectively corrects this problem by providing linear homothetic expansion with respect to the centre of the yield surface.A very compact implicit integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Expected consequences might concern the predicted stability of the constitutive response, a subject so far never explored from this standpoint. When documented, convexity‐related issues might be remedied by resorting to recent convexification techniques …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expected consequences might concern the predicted stability of the constitutive response, a subject so far never explored from this standpoint. When documented, convexity‐related issues might be remedied by resorting to recent convexification techniques …”
Section: Discussionmentioning
confidence: 99%
“…When documented, convexity-related issues might be remedied by resorting to recent convexification techniques. 74,75 The discussion offered in this work also aimed to discourage simplistic use of viscoplasticity as a mere numerical expedient against mesh dependence in strain-localisation problems. Conversely, the viscoplastic framework was reappraised as a physically sound approach to sand modelling, easy to extend to nonlocality whenever also characteristic length effects are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…with the initial yield surface size controlled by p c0 [67]. B p represents the slope of the ε p ν − lnp ′ curve [65] and can be related to the conventional MCC parameters by (detailed in the Appendix):…”
Section: Constitutive Modelmentioning
confidence: 99%
“…The MCC model developed by Panteghini and Lagioia [67,68], which was adopted in the study, has advantages in convergence and integration efficiency by using fewer unknowns and improved yield functions with full convexity and homothety. For the elliptical yield surface used in the present study, the new expression is given by:…”
Section: Constitutive Modelmentioning
confidence: 99%
“…An extensive literature review performed by Franchi et al on yield functions revealed the extent of the ambiguity and confusion regarding the requirements of convexity. However, the discussion on convexity has been more recently reopened (Gluege and Bucci), and remedies have been proposed to provide convexity to non‐convex functions (Panteghini and Lagioia,) Lagioia et al, and Lagioia and Panteghini.…”
Section: Hyper‐elasticitymentioning
confidence: 99%